The biology and physical ecology of Apanteles subandinus Blanchard (Hymenoptera : Braconidae), with notes on the temperature responses of Apanteles, Scutellaris Muesebeck and their host, the potato tuber worm. (1971)
Papa-Solanum tuberosum